Analysis Dynamics Group In Environment School : Cooperation Between Teachers And The Implementation Of Group Work For Students At UPT SPNF, Medan City - Rhasya Adhira Putri Hasbianda; Emi Sofya Pratiwi Silitonga; Naila Nafisah Zulfa (PT. Padang Tekno Corp, 2026)
This study aims to describe the group dynamics within the school environment, focusing on teacher collaboration and the implementation of group work among students at UPT SPNF Kota Medan. This descriptive research provides an overview of how collaborative relationships among teachers develop and how group work is applied during the learning process. Data were collected through observations and questionnaires to obtain information related to interaction patterns, levels of participation, and the effectiveness of cooperation within the school setting. The findings indicate that teacher collaboration is in a good category and contributes significantly to creating a more conducive learning atmosphere. Additionally, the implementation of group work among students enhances their communication skills, responsibility, and social interaction. These results highlight that effective group dynamics play a crucial role in improving the quality of learning processes and outcomes in the school environmen